2018
DOI: 10.1021/acsnano.8b03273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ligand-Controlled Emission in Silicon Nanoparticles

Abstract: Although bulk silicon (Si) is known to be a poor emitter, Si nanoparticles (NPs) exhibit size-dependent photoluminescence in the red or near-infrared due to quantum confinement. Recently, it has been shown that surface modification of Si NPs with nitrogen-capped ligands results in bluer emission wavelengths and quantum yields of up to 90%. However, the emission mechanism operating in these surface-modified Si NPs and the factors that determine their emission maxima are still unclear. Here, the emission in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
(111 reference statements)
0
21
0
Order By: Relevance
“…At the same time, several recent studies have reported multimodal PL relaxation spanning a range of wavelengths and time scales, where the faster modes have been attributed to both surface effects and quasi-direct recombination, although the distinction between the two is becoming increasingly blurred. In studies directed at extending the range of visible SiNC luminescence to shorter wavelengths, recent focus has been on bright size-independent emission tuned through a variety of complex surface ligands, with the primary role of the Si core being optical absorption, and where PL color is determined by the charge-transfer characteristics of the ligands as opposed to quantum confinement.…”
mentioning
confidence: 99%
“…At the same time, several recent studies have reported multimodal PL relaxation spanning a range of wavelengths and time scales, where the faster modes have been attributed to both surface effects and quasi-direct recombination, although the distinction between the two is becoming increasingly blurred. In studies directed at extending the range of visible SiNC luminescence to shorter wavelengths, recent focus has been on bright size-independent emission tuned through a variety of complex surface ligands, with the primary role of the Si core being optical absorption, and where PL color is determined by the charge-transfer characteristics of the ligands as opposed to quantum confinement.…”
mentioning
confidence: 99%
“…In particular, the unique hydrophilic and optical properties of ES-SiNPs were probably attributable to their massive naturally modifying proteins secreted from yeast. 34,44 Long-Term Cellular Imaging. As fluorescent probes, the cytotoxicity of ES-SiNPs is necessary to be evaluated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The FTIR results are consistent with those of XPS, and it is therefore reasonably deduced that the above-mentioned yeast-derived proteins played a crucial role as reductants and stabilizers in the biomimetic synthesis of ES-SiNPs. In particular, the unique hydrophilic and optical properties of ES-SiNPs were probably attributable to their massive naturally modifying proteins secreted from yeast. , …”
Section: Resultsmentioning
confidence: 99%
“…Si NPs have been shown to have high quantum efficiency [539] . The mechanism for emission is a charge transfer state between the ligand and the Si NP surface [540] . This charge transfer emission has been shown to produce non-classical light, as photon antibunching measurements have shown g (2) (0) values as low as 0.05 with high dependence on the substrate and ligand [541] .…”
Section: Other Colloidal Emittersmentioning
confidence: 99%